Analisis Strategi Bauran Pemasaran Dalam Upaya Meningkatkan Penjualan Produk Asuransi Syariah PT. Asuransi Jiwa Syariah Bumiputera Cabang Medan - Gunara, Dendy Irwan; M. Nawawi,, Zuhrinal; Aslami, Nuri (IAI Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the marketing strategy through the 4P marketing mix implemented by PT. The Medan branch of Bumiputera sharia life insurance is able to compete in the market and increase sales. This study used descriptive qualitative methods. Data collection techniques used interviews and questionnaires. The results of this research show that the results of this research prove that the IFE score of 3.22 proves a solid internal position, the EFE score of 2.7 proves that the industry responds to the opportunities that exist and stays away from threats in its industrial market. The Cartesian chart shows that the position of the industry in rough conditions is very profitable for the industry. In the IE matrix for the IFE and EFE profit sharing, the IFE score is 3.22 and the EFE profit share is 2.7 if converted into the IE Matrix chart, so that it is in box 5, where the results of the industry enter where the results are Focus Strategy through horizontal integration (cells 2 and 5). With the method of using profit economies of scale both in creation and sales, whereas if this industry is located in a moderately attractive industry, the strategy that is inaugurated is confirmation (cell 5). The goal is relatively more defensive, is to avoid running out of marketing and running out of profits. Industries located in this cell can expand markets, manufacturing facilities, and technology through internal or external development through acquisitions or joint ventures with other industries in similar factories. The industry's SWOT matrix lies in the SO box, So the marketing mix strategy implemented is good and running well the role of the marketing strategy through the aspects of product, price, people and process can compete in the market and is felt to be able to increase sales. Keywords: marketing mix strategy, life insurance, IFE, EFE, IE, SO.